Relationship between delivery type and postpartum sexual activity - Heidari, M; Merghati Khoei, E; Valaei, N (Advances in Nursing & Midwifery, 2010)
Background and aim Today, women have a tendency for cesarean. One of the reasons is thought to be their belief in the effect of normal delivery on postpartum sexual activities. With respect to the high rate of cesarean in Tehran and lack of enough evidence in this regard, this historical cohort study was conducted to identify a relationship between delivery type and postpartum sexual activity of women referring to selected healthcare centers of Tehran in 2009. Material and methods This study is to historical cohort reason of sexual activities of 140 women with vaginal delivery (case group) were compared with 140 women with cesarean (control group). A questionnaire regarding demographics and sexual activities was used for data collection, validated and made reliable by content and test-retest methods respectively. Data were analyzed by different statistical methods with Spss 13. Findings A significant relationship was found between income as well as educational level of women and selection of delivery type (P<0.20, P<0.001). A significant relationship was also found between onset of sex and delivery type (P<0.002) as 45% of women with normal delivery and 60.7% of women with cesarean had 3 times or less sex in a month. No significant difference was found between the groups after delivery in terms of changes in sexual desire and satisfaction, orgasm, pain during sex and vaginal dryness compare with antepartum period. Conclusion It seems that no significant relationship exists between delivery type and postpartum sexual activities. Keywords: Delivery type, Sexual activities, Vaginal delivery, Cesarean. *Corresponding Author: Masoomeh, heidari. College of Nursing and Midwifery, Shahed University, Tehran, Iran E-mail: heidari@shahed.ac.ir